Efeito do bloqueio das proteÃnas hsp90 sobre a sensibilidade a antifÃngicos e produÃÃo de fatores de virulÃncia no complexo Cryptococcus neoformans/C. gattii - Antonio JosÃ de Jesus Evangelista (2015)
Cryptococcus neoformans species Complex comprises the main agents of cryptococcosis, an important systemic mycosis of nature and opportunistic. These species are capable of expressing multiple virulence factors that contribute to the development of resistance to antifungal therapeutic use. Research seeking new effective therapy measures are necessary. Heat shock proteins (Hsp) have been shown to be a promising molecular target for medical treatment of various diseases such as various forms of cancer and atherosclerosis. Studies have demonstrated that the expression of these chaperonins is also required for the maintenance of cellular homeostasis in different fungal pathogens. From this perspective, this study aimed to investigate the effect of blocking the protein Hsp90 front of sensitivity to antifungal agents in vitro planktonic cells and sessile, production of virulence factors in vitro and in vivo virulence in Cryptococcus neoformans species Complex. Therefore, the action of yeast Hsp90 protein was blocked with radicicol drug - an antibiotic capable of inhibiting the ATPase activity of Hsp90 - and then the cultures were evaluated for in vitro susceptibility to antifungal agents for therapeutic use in planktonic cells and associated in biofilms. We also assessed the effect of inactivation of Hsp90 on the production of virulence factors capsule, melanin and proteases. In addition, the in vivo virulence was investigated in a model of experimental infection using the nematode Caenorhabditis elegans. The results revealed that radicicol inhibited the growth of planktonic cells Cryptococcus spp. (n=12) with values of minimum inhibitory concentration (MIC) ranging from 0.5 to 2 μg/mL. We observed synergy between pharmacological and radicicol azoles. Furthermore, blockade of Hsp90 potentiated the effect of in vitro antifungal agents, particularly for the fluconazole and itraconazole, which MIC values were reduced by up to 64 times the face of isolated cells (n=12). Although the blockade of Hsp90 by isolated radicicol was not able to inhibit biofilm formation and biofilm formed of Cryptococcus spp. (n=12) (p>0.05), the inactivation of Hsp90 potentiated the effect of amphotericin B, azoles, especially fluconazole, when tested in combination with radicicol (p<0.05). Moreover, blockade of Hsp90 significantly reduced the volume of capsular Cryptococcus spp. (n=4) (p<0.05). However, no difference was observed in production of melanin by radicicol treated cells (n=4) (p>0.05) as well as the production of protease by strains of Cryptococcus spp. (n=4) (p>0.05). By contrast, inactivation of Hsp90 decreased virulence Cryptococcus spp. in vitro and in vivo in C. elegans (p<0.0001) as well as maximize the effect of fluconazole in vitro and in vivo. Therefore, Hsp90 is an important target for the development of antifungal strategies. However, further studies are needed to better understand the role of Hsp90 in fungal pathogens of the genus Cryptococcus spp.